Promise or Peril? Electronic Technologies, Equity, and Marginalized Students - Denise M. Dalamio (Educational Considerations, 1999)
The ability to access electronic mail (e-mail), the Internet (Net), and the World Wide Web (Web) have become life skills for the 21st century. Internet users have almost instant access to facts, figures, databases, public archives, libraries, and information from around the world.